Distances Covered above and below the Anaerobic Threshold by Professional Football Players in Different Competitive Conditions - Marcin Andrzejewski (Central European Journal of Sport Sciences and Medicine, 2015)
In modern endurance training information about an athlete’s performance below and above the anaerobic threshold is crucial. The aim of the present study was a comparative analysis of the total distance covered by football players in two rounds of the 2013/1014 playing season. Furthermore, the study also assessed the performance of elite Bundesliga players during competitive matches, above and below the running speed of 4 m·s –1, corresponding to the level of anaerobic threshold (AT). The players’ mean body height was 183.00 ±6.44 cm, body mass 78.19 ±7.42 kg, and mean age was 27.99 ±3.47 years. The analysis was carried using the Impire AG motion analysis system on the basis of official match reports from the Deutscher Fußball-Bund (DFB). The study revealed that the total distance covered by the players in match-play was significantly shorter in the second round of the playing season. The distance covered by the players below the AT is significantly shorter in the spring round than in the autumn round, while the distance covered above the AT shows a reverse, although non-significant tendency. In the spring round the volume of players’ work performed above the anaerobic threshold is greater than the volume of exercise performed below the AT.